Long COVID risk factors and outcomes among solid organ transplant recipients: a retrospective cohort study - Sandoval, Micaela N.; Moore, Linda W.; Huang, Howard J.; Graviss, Edward A. (Frontiers in Surgery, 2025)
BackgroundSolid organ transplant (SOT) recipients are not only at increased risk of morbidity and mortality due to acute COVID-19 but may also experience poor long-term outcomes due to post-acute COVID-19 syndromes, including long COVID.MethodsThis retrospective, registry-based chart review evaluated graft failure and mortality among SOT recipients diagnosed with COVID-19 at a large, urban transplant center in Houston, Texas, USA. Patient populations were analyzed separately according to their long COVID status at the time of transplant to preserve the temporal relationship between the exposure (long COVID) and the outcome (graft failure or mortality).ResultsIn total, 146 (5%, 146/3,202) patients were diagnosed with long COVID, 443 (14%, 443/3,202) patients expired during the study period, and 202 (6%, 202/3,202) were diagnosed with graft failure. Overall, patients with long COVID were older, had an increased comorbidity burden, and were more likely to be lung, heart, or heart–lung recipients compared with those who were not diagnosed with long COVID. Long COVID was not significantly associated with death or graft failure in this study population, though relationships varied across subpopulations.ConclusionsThe observed differences between patients diagnosed with COVID-19 and long COVID before and after transplant warrant additional studies as the proportion of people with some SARS-CoV-2 infection history approaches 90%. Future investigations may prioritize longitudinal follow-up of long COVID patients diagnosed before or after transplant to determine specific etiologies of long-term morbidity and mortality.